1982
DOI: 10.1021/es00097a005
|View full text |Cite
|
Sign up to set email alerts
|

Multitechnique screening of Chicago municipal sewage sludge for mutagenic activity

Abstract: A sample of anaerobically digested Chicago municipal sewage sludge has been examined for mutagenicity by using a variety of biological assays with different genetic end points. The sludge clearly contains components that induce mutagenic responses in all of the species employed. Acetone extracts from the equivalent of 155 pL of neat sludge induced a doubling in the number of revertant colonies of the Ames Salmonella typhimurium strain TA98 after activation with mammalian microsomes. In situ and laboratory stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 7 publications
3
26
0
Order By: Relevance
“…This procedure is similar to that described by others in their studies of wastewaters in which various XAD resins were employed for residue organic concentration (e.g., Rappaport et al, 1979;Baird et al, 1980;Hopke et al, 1982;Johnston et aI., 1982). Also, our method is based on our XAD procedure originally described for the concentration of residue organics from drinking water (Loper and Tabor, 1982;Loper et al, 1982).…”
Section: Discussionmentioning
confidence: 84%
“…This procedure is similar to that described by others in their studies of wastewaters in which various XAD resins were employed for residue organic concentration (e.g., Rappaport et al, 1979;Baird et al, 1980;Hopke et al, 1982;Johnston et aI., 1982). Also, our method is based on our XAD procedure originally described for the concentration of residue organics from drinking water (Loper and Tabor, 1982;Loper et al, 1982).…”
Section: Discussionmentioning
confidence: 84%
“…One study (Hopke et al 1982) has found mutagenic effects in the above-ground parts of plants grown on sludge-treated soil. These results would imply crop uptake of unknown contaminants.…”
Section: Nickelmentioning
confidence: 99%
“…A multitechnique screening of Chicago municipal sewage sludge for mutagenic activity was recently reported by Hopke et al 196 The chemical fractionation technique was based on a sequential extraction with different solvents. The sewage sludge was centrifuged at 12500 rpm for 60 min.…”
Section: E Municipal and Industrial Waste Watersmentioning
confidence: 99%